Healthcare Reform in China From Violence To Digital Healthcare - Milcent, Carine (Springer International Publishing, 2018)
How efficient is the Chinese healthcare system? Milcent examines the medication market in China against the global picture of healthcare organization, and how public healthcare insurance plans have been implemented in recent years, as well as reforms to tackle hospital inefficiency. Healthcare reforms, demographic changes and an increase in wealth inequity have altered healthcare preferences, which need to be addressed. Significantly, the patient-medical staff relationship is analysed, with new proposals for different lines of communication. Milcent puts forward digital healthcare in China as a tool to solve inefficiency and rising tensions, and generate profit. Where China is leading in the digitalization of healthcare, other countries can learn important lessons. Chinese social models are also put into context with respect to current reforms and experimentation.